Formation of New Ligands Imine- (Oxazole, Thiazole, Thiophene) And Study of (Chemical Investigation and Chromatographic Applications) - N. Mohamed Salih, Mostafa; Noor ObaidAl-Husseini, Zaid; Mahmood Aljamali, Nagham (International Journal of Engineering and Technology, 2018)
(Oxazole, Thiazole, Thiophene) derivatives- Imine ligands were synthesized in this paper by using  many  reactions such as cyclization  reaction,  chalcone  reaction  in  basic  medium, condensation  reaction  to format four new ligands included heterocycles represented by oxazole, thiophene, thiazole derivatives with imine group in same compounds. The four ligands have been identified by several methods such as spectra of (UV-Visible investigation, 1H NMR, FT.IR) and study of chromatographic applications for all ligands.